Acoplando um modelo de doenças ao modelo cropgro-soybean : ferrugem asiática da soja - Pedrini, João Eduardo (2010)
Quantifying the impact of Asian Soybean rust on yield is of great interest. Mathematical models have been developed representing the relationship between disease intensity yield. These models, admittedly useful, are based on empirical relationships determined either under eld or controlled conditions. By the other hand, the CSM-CROPGRO-Soybean model contained within DSSAT (Decision Support System for Agro-Technology Transfer) simulates plant growth and development from sowing to maturity using a daily time step, and ultimately predicts yield. The CSM-CROPGROSoybean model like the majority of crop simulation models was developed in FORTRAN. Therefore, one of the main challenges to the crop simulation models community is the integration of scienti c models created by di erent groups, which should expand the usefulness of the coupled new model. In coupling, aspects that should be considered include the identi cation of appropriate models, speci cations of interactions and the possibility of dynamic coupling di erent source codes. Therefore, there is a need to build a structural component containing the interface and the communication protocols between the components of the system. Beyond these stages, it is necessary to choose an adequate approach to couple the models. Integrating di erent aspects of a crop simulation model that mimics the growth and development of soybean and also accounts for the Asian Soybean Rust impacts on yield should be useful for analyzing and implementing disease management practices. Using di erent techniques of programming and coupling approaches was possible to develop a modi ed CSM-CROPGRO-Soybean that responded to rust intensity. The determination of best practices for achieving high yields while environmentally and economically sustainable is valuable information for strategic plans in Brazil and elsewhere. However, using the conventional experimental approach should consume a signi cant amount of time and resources. The use of crop simulation models, may be an alternative option for understanding crop response under various conditions of growth. The model CSM-CROPGRO-Soybean,coupled to a disease model, dynamically represents the Asian rust soybean progress and its impact on yield. Crop coecients for CSM-CROPGRO-Soybean were obtained from the DSSAT data base. The parameters for the soybean rust were obtained either from literature or estimated from experimental data. Weather data and soil characteristics from Passo Fundo, RS, Brazil were used to evaluate the modi ed model CSM-CROPGRO-Soybean. A sequence of observed categorical data representing soybean rust intensity in the area was used for model comparison. The results showed that the coupled model represented reasonable well the impact on yield due to rust colonization. In the simulation, soybean yield was less a ected in years when disease was considered of low intensity and signi cantly a ected in years categorized of high intensity.